PREVALENCE AND DETERMINANTS OF DEPRESSION AMONG ADOLESCENT STUDENTS IN RURAL AREAS SURROUNDING BHUBANESWAR, ODISHA: A CROSS-SECTIONAL STUDY. - Dr. (Maj) Mohanty Rajesh Priyadarsan; Dr Aparna Aradhana; Dr Nitish Jena; Panda, Dr Suchismita (Student’s Journal of Health Research Africa, 2025)
Introduction Depression, a persistent low mood and aversion to activity, significantly affects thoughts, behavior, and well-being, often emerging during adolescence—a phase of rapid physical, emotional, and social changes. Globally, around 20% of adolescents experience psychological disorders, with depression being the most common. Aim and objectives: To assess the prevalence and associated factors of depression among adolescent students in rural areas surrounding Bhubaneswar, Odisha. Material and methods This community-based cross-sectional study was conducted at Ekamra College, Sundarpada, a rural area near Bhubaneswar, Odisha, targeting 11th and 12th-grade students. Exclusions included those with major physical illnesses or diagnosed psychiatric conditions. The study included 220 participants (110 males and 110 females) selected based on roll numbers. Depressive symptoms were assessed using the Beck Depression Inventory (BDI), with students completing the questionnaire based on their feelings over two weeks. Results with a mean age of 17 years; the majority (44.54%) were 18 years old. Most participants (84.10%) were Hindus, with 77.29% belonging to the general caste and 22.71% to OBC, SC, or ST categories. The study revealed that 70% of male and 76% of female students experienced depression, ranging from borderline clinical depression to extreme depression. Conclusions This study explores depression among rural adolescents in Odisha, identifying sleep duration, outdoor activities, socioeconomic status, parental conflicts, and education as key contributors. Addressing these stressors through improved habits, socioeconomic support, and healthier family dynamics could reduce depression, highlighting the need for targeted interventions in rural youth mental health. Recommendations Regular mental health screening programs should be implemented in schools to identify adolescents at risk of depression. Teachers and school staff should be trained to recognize early signs of depression and refer students for further evaluation.